DESIGN METHODOLOGY OF RISK-ORIENTED INTERNAL CONTROL SYSTEM OF A BANK - Novashina,; Karpunin,; Efremova, (Revista Inclusiones, 2020)
The article is devoted to a fundamentally new concept of the methodology for building the system of risk-oriented internal control in a bank. The authors use the system paradigm as the basic and key principle of the methodology for designing and building the bank's internal control system. The bank is viewed as a complexly organized socio-economic system, consisting of structural components – that is, functional subsystems of the bank, forming a new quality in their integrated unity - a deposit and credit institution. The second key component of the applied methodology is the principle of the system-functional organization, based on the understanding that each institutional component of the system - the internal structural and functional divisions of the bank (divisions, departments, management) when designed should be endowed with a necessary and sufficient set of specific functions. The third key component of the applied methodology is the principle and a special system requirement: the bank's internal control system is designed to perform a key function of providing feedback in the system. The presence of the feedback in a system of any type is a necessary condition for the existence of this system.